Dose-escalated simultaneously integrated boost photon or proton therapy in pancreatic cancer in an in-silico study: Gastrointestinal organs remain critical. (March 2021) - Stefanowicz, Sarah; Wlodarczyk, Waldemar; Frosch, Susanne; Zschaeck, Sebastian; Troost, Esther G.C.
Highlights: Robustly optimized proton plans (rMFO-IMPT) with simultaneously integrated boost (SIB) were clinically applicable. Gastrointestinal organs reached critical dose values in rMFO-IMPT, VMAT and Tomotherapy techniques. rMFO-IMPT significantly reduced the low and intermediate dose to organs at risk. No clinically significant differences on results depending on tumor location or surgical status were observed. Abstract: Purpose: To compare the dosimetric results of an in-silico study among intensity-modulated photon (IMRT) and robustly optimized intensity-modulated proton (IMPT) treatment techniques using a dose-escalated simultaneously integrated boost (SIB) approach in locally recurrent or advanced pancreatic cancer patients. Material and methods: For each of 15 locally advanced pancreatic cancer patients, a volumetric-modulated arc therapy (VMAT), a Tomotherapy (TOMO), and an IMPT treatment plan was optimized on free-breathing treatment planning computed tomography (CT) images. For the photon treatment plans, doses of 66 Gy and 51 Gy, both as SIB in 30 fractions, were prescribed to the gross tumor volume (GTV) and to the planning target volume (PTV), respectively. For the proton plans, a dose prescription of 66 Gy(RBE) to the GTV and of 51 Gy(RBE) to the clinical target volume (CTV) was planned. For each SIB-treatment plan, doses to the targets and OARs were evaluated and statistically compared. Results: All treatment techniques reached the prescribed doses to the GTV and CTV or PTV. The stomach and the bowel, in particular the duodenum and the small bowel, were found to be frequently exposed to doses exceeding 50 Gy, irrespective of the treatment technique. For doses below 50 Gy, the IMPT technique was statistically significant superior to both IMRT techniques regarding decreasing dose to the OARs, e.g. volume of the bowel receiving 15 Gy ( V 15Gy ) was reduced for IMPT compared to VMAT ( p  = 0.003) and TOMO ( p  < 0.001). Conclusion: With all photon and proton techniques investigated, the radiation dose to gastrointestinal OARs remained critical when treating patients with unresectable locally recurrent or advanced pancreatic cancer using a dose-escalated SIB approach.